Предмет: Алгебра,
автор: kkkkiiiii
Выполните действия используя формулы сокращенного умножения:
a)(a√3+√x)(a√3-√x)
б)(2√х-√3у)²
в)(√3-√t)(3+t+√3t)
Ответы
Автор ответа:
0
Решение
a)(a√3+√x)(a√3-√x) = (a√3)² - (√x)² = 3a² - x
б)(2√х-√3у)² = (2√x)² - 2*(2√x)*(√3y) + (√3y)² = 4x - 4√(3xy) + 3y
в)(√3-√t)(3+t+√3t) = (√3)³ - (√t)³
a)(a√3+√x)(a√3-√x) = (a√3)² - (√x)² = 3a² - x
б)(2√х-√3у)² = (2√x)² - 2*(2√x)*(√3y) + (√3y)² = 4x - 4√(3xy) + 3y
в)(√3-√t)(3+t+√3t) = (√3)³ - (√t)³
Автор ответа:
0
Спасибо огромное
Похожие вопросы
Предмет: Алгебра,
автор: mledenev392
Предмет: Математика,
автор: ayxanm568
Предмет: Геометрия,
автор: vlada1285vlada
Предмет: География,
автор: МММаааНННяяя